A methodological proposal to research patients’ demands and pre-test probabilities using paper forms in primary care settings - Gusso, Gustavo Diniz Ferreira (2013)
Objective: The purpose of this study is to present a methodology for assessing patients’ demands and calculating pre-test probabilities using paper forms in Primary Care. Method: Most developing countries do not use Electronic Health Records (EHR) in primary care settings. This makes it difficult to access information regarding what occurs within the health center working process. Basically, there are two methodologies to assess patients’ demands and problems or diagnosis stated by doctors. The first is based on single attendance at each appointment, while the second is based on episodes of care; the latter deals with each problem in a longitudinal manner. The methodology developed in this article followed the approach of confronting the ‘reason for the appointment’ and ‘the problem registered’ by doctors. Paper forms were developed taking this concept as central. All appointments were classified by the International Classification of Primary Care (ICPC). Discussion: Even in paper form, confrontation between ‘reason for the appointment’ and ‘problem registered’ is useful for measuring the pre-test probabilities of each problem-based appointment. This approach can be easily reproduced in any health center and enables a better understanding of population profile. Prevalence of many illnesses and diseases are not known in each reality, and studies conducted in other settings, such as secondary and tertiary care, are not adequate for primary health care. Conclusion: This study offers adequate technology for primary health care workers that have potential to transform each health center into a research-led practice, contributing directly to patient care.